2021
DOI: 10.1007/s11606-021-06899-y
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implant Safety: an Overview of Current Regulations and Screening Guidelines

Abstract: Breast implant surgery for cosmetic or reconstructive purposes is becoming increasingly common. While the devices used are regulated and approved by the US Food and Drug Administration, all patients with breast implants require continued follow-up. Many patients will seek this care from their primary care providers, especially when follow-up with their plastic surgeon is difficult. It is vital that treating clinicians are knowledgeable about the history of breast implants, routine screening guidelines, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…17,18 At the same time, some experts believe that silicone breast implants are not associated with BII, because many reported symptoms may have other causes, such as genetic susceptibility and family history of the patient, and there is no appropriate control group. 19 Cohen Tervaert et al 17 confirmed that silicone breast implants may lead to autoimmune diseases in genetically In this study, we analyzed the adverse events of breast implants that were reported to the FDA's MAUDE database from July 2019 to June 2022. Furthermore, by analyzing the local complications and BII of breast implants, we hope to make women who want breast implants think more about whether it is worth it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 At the same time, some experts believe that silicone breast implants are not associated with BII, because many reported symptoms may have other causes, such as genetic susceptibility and family history of the patient, and there is no appropriate control group. 19 Cohen Tervaert et al 17 confirmed that silicone breast implants may lead to autoimmune diseases in genetically In this study, we analyzed the adverse events of breast implants that were reported to the FDA's MAUDE database from July 2019 to June 2022. Furthermore, by analyzing the local complications and BII of breast implants, we hope to make women who want breast implants think more about whether it is worth it.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have found that silicone breast implants are associated with an increased risk of autoimmune diseases such as systemic sclerosis, Sjögren syndrome, and sarcoidosis 17,18 . At the same time, some experts believe that silicone breast implants are not associated with BII, because many reported symptoms may have other causes, such as genetic susceptibility and family history of the patient, and there is no appropriate control group 19 . Cohen Tervaert et al 17 confirmed that silicone breast implants may lead to autoimmune diseases in genetically susceptible individuals, but they also failed to fully consider and correct some confounding factors, such as changes in microbiome, the presence of other chemical factors, and patients’ diet, hormone levels, and psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, primary care physicians should actively screen for breast implant-related pathology when patients present with nonspecific signs or symptoms suggesting these complications and refer them to a specialized clinic when needed, especially considering the fact that BIA-ALCL has a favorable prognosis when discovered early. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…A notable contribution was the article by McKernan et al, which was directed at guiding internal medicine physicians to better understand and handle BIA-ALCL cases. 13 The role of The National Comprehensive Cancer Network guidelines on BIA-ALCL have been recognized by the US Food and Drug Administration and widely advocated by other national specialty societies. These guidelines have helped create a standardized treatment for BIA-ALCL at all stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A notable contribution was the article by McKernan et al, which was directed at guiding internal medicine physicians to better understand and handle BIA-ALCL cases. 13 The role of The National Comprehensive Cancer Network guidelines…”
Section: Takeawaysmentioning
confidence: 99%